Risk-oriented approach of state control (supervision) and municipal control in relation to secondary schools (sociological survey) - S. E. Titor (Вестник университета)
The control and supervisory activities’ reforms in Russia are actively underway: a risk-oriented model during organising the control (supervision) is being introduced. Some control and supervisory agencies implement such model from 2015. The Federal Service for Supervision of Education, despite the lack of a legislative framework at the federal level, recommended to the regions to implement elements of a risk-based model independently. In this regard, it is important to analyse what has changed for educational organisations, what is their attitude to new forms and methodologies of control (supervision). The analysis will make it possible to more thoroughly determine the directions of state policy implementation in the field of risk-oriented model of control and supervisory activities, adjust mechanisms, and adopt appropriate recommendations.